Formulation and Antibacterial Activity of Garlic Bulbs Ethanol Extract Shampoo Against Staphylococcus aureus - Sabrina Krisna Whardhani; Elisa Vica Sharonita; Jessica Novia; Febbyasi Megawaty Rangka (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2026)
Dandruff is a scalp condition characterized by the excessive shedding of dead skin cells, often exacerbated by Staphylococcus aureus. This study explores the potential of garlic bulbs extract as an antibacterial agent in shampoo formulations to address dandruff. This approach offers a safer alternative to Zinc Pyrithione (ZnPT), which can cause side effects such as scalp dermatitis, hair damage, and discoloration. This study aimed to formulate an herbal shampoo containing garlic bulbs ethanol extract and evaluate its physical properties and antibacterial activity against Staphylococcus aureus. Three formulations, F1 (6%), F2 (8%), and F3 (10%), were prepared and assessed for organoleptic characteristics, pH, foam height, viscosity, homogeneity, and stability through cycling tests. Antibacterial activity was determined using the well diffusion method. The inhibition zone diameters obtained were 19.80 mm (F1), 23.65 mm (F2), and 25.73 mm (F3), with inhibition categories classified according to CLSI as intermediate for F1 and susceptible for both F2 and F3. Increasing extract concentration improved antibacterial activity; however, F2 was identified as the optimal formulation due to its strong inhibition (23.65 mm), stable physical characteristics, and more efficient extract utilization compared to F3. All formulations fulfilled Indonesian National Standard (SNI) requirements and remained stable after six cycling cycles. These findings demonstrate that garlic bulbs extract shampoo possesses significant antibacterial activity against Staphylococcus aureus and exhibits suitable physical stability, supporting its potential as a safer herbal alternative for dandruff management.